(untitled) (Research, Society and Development, 2024)
Considering teenage pregnancy as a public health problem in Brazil, the main objective of this study is to find out the reality of teenage pregnancy in the country; the existing public health policies aimed at this issue; the official national, state and regional records and data around the issue. It is a quantitative study, carried out using multi-methods in order to provide a greater approximation and depth of knowledge about the phenomenon of teenage pregnancy, which allowed for a qualitative analysis of the issue in the Alta Paulista region where the study was carried out. A systematic literature review was used, as well as a study of the state of the art and the collection of quantitative data from the cities that make up the research universe on official websites and websites of recognized research entities/institutions. The data collected was treated with quantitative and qualitative analysis and presented in tables followed by an analytical discussion. The research reveals that the percentage of teenage pregnancies in the region represents around 10% of pregnancies over the studied period, confirming a worrying proximity to the data published by the WHO. Given this context, the study allows us to conclude that these municipalities, as well as other regions of the country, lack public policies, programs and actions aimed at preventing teenage pregnancies, broadening debates and breaking paradigms based on taboos and mistaken moral interpretations about sex education and the reproductive health of young girls.